A randomized study of a best practice alert for platelet transfusions. Issue 1 (3rd June 2021) - Murphy, Colin; Mou, Eric; Pang, Emily; Shieh, Lisa; Hom, Jason; Shah, Neil
Abstract: Background and Objectives: Inappropriate platelet transfusions represent an opportunity for improvements in patient care. Use of a best practice alert (BPA) as clinical decision support (CDS) for red cell transfusions has successfully reduced unnecessary red blood cell (RBC) transfusions in prior studies. We studied the impact of a platelet transfusion BPA with visibility randomized by patient chart. Materials and Methods: A BPA was built to introduce CDS at the time of platelet ordering in the electronic health record. Alert visibility was randomized at the patient encounter level. BPA eligible platelet transfusions for patients with both visible and non‐visible alerts were recorded along with reasons given for override of the BPA. Focused interviews were performed with providers who interacted with the BPA to assess its impact on their decision making. Results: Over a 9‐month study period, 446 patient charts were randomized. The visible alert group used 25.3% fewer BPA eligible platelets. Mean monthly usage of platelets eligible for BPA display was 65.7 for the control group and 49.1 for the visible alert group ( p  = 0.07). BPA‐eligible platelets used per inpatient day at risk per month were not significantly different between groups (2.4 vs. 2.1, p  = 0.53). Conclusion: It is feasible to study CDS via chart‐based randomization. A platelet BPA reduced total platelets used over the study period and may have resulted in $151, 069 in yearly savings, although there were no differences when adjusted for inpatient days at risk. During interviews, providers offered additional workflow insights allowing further improvement of CDS for platelet transfusions.